Food politics : how the food industry influences nutrition and health - Nestle, Marion (California studies in food and culture, 2007)
Synopsis: How does the food industry influence what we eat and, therefore, our health? What are the food industry's marketing methods and what is its relationship to the political system? What can be said about its use of political power to achieve profit goals? A bold, unprecedented behind-the-scenes expose of one of America's biggest and most powerful industries.